Retinol deficiency in animals: Etiopathogenesis and consequences - P. M. Skliarov; S. Y. Fedorenko; S. V. Naumenko; O. V. Onischenko; K. О. Holda (Regulatory Mechanisms in Biosystems, 2020)
Infertility is widespread for all species of animals and causes significant economic losses to livestock due to the loss and shortage of offspring, their reduced viability and, consequently, increased morbidity and mortality. Alimentary-deficiency factors are among the commonest causes of infertility, from which A-vitamin deficiency should be singled out. The precursor of vitamin A in the body is carotene, which is an unstable compound which is easily destroyed even under the influence of moderate factors of influence, in connection with which its deficiency is global, especially at the end of the winter – stall period of keeping animals. Accordingly it is the leading etiological factor of retinol deficiency infertility. As a result, the body has two negatives that act in parallel: carotene / vitamin A deficiency adversely affects the organs, the constituent and major functional unit of which is the secretory epithelial cell, and the free radical oxides formed in high concentration are extremely effective in destroying the cells, weakening antioxidant protection. Vitamin A has a significant effect on the reproductive function of animals both directly and indirectly. It is necessary to ensure the structure and functioning of the epithelial tissues of the organs of regulation and performance of sexual function, and therefore the physiological development of the fetus and the course of pregnancy, parturition and postpartum period, ovo- and spermiogenesis, the manifestation of sexual reflexes. Instead, its deficiency underlies the etiology and pathogenesis of retinol deficiency infertility of animals, causing changes in individual indices of homeostasis and prooxidate-antioxidant system, morphostructure of the reproductive and endocrine organs, hormonal status, sperm quality and reproductive function. The consequence is the emergence and development of gynecological, andrological, mammological and perinatal (ante-, intra-, post- and neo-) pathologies. At the same time, the addition of carotene or retinol to the diets of animals or their oral administration in cases of deficiency of vitamin A prevents impaired reproductive function. The study of the features of the etiopathogenesis of retinol deficiency infertility of animals allows programs of complex diagnostics, therapy and prevention to be developed which provide determination of carotene and vitamin A content and replenishment of the organism in cases of their deficiency.